(untitled) (Research, Society and Development, 2022)
Objective: To identify initiatives that demonstrate the co-production of patient-centered care during hospitalization. Method: Qualitative, exploratory-descriptive study, with triangulation of multiple data sources: document analysis, observation of 10 professionals and 24 interviews with patient-families. Thematic analysis followed the concept of co-production. Results: Paths covered and to be covered emerged from the participants’ perceptions about the coproduction of patient-centered care, channeled in quality and safety of care, information and guidance as a subsidy to participate in treatment, attention to rights and duties, and meeting health needs. Conclusions: Although the potential for co-production towards patient-centered care has been identified, there are paths to go, in the qualification of the care of the needs demanded by patients and families. It is considered that the patient’s experience in the process of hospital care, when guided by the assumptions of patient safety, leads to the co-production of patient-centered care and promotes the overcoming of barriers to the advancement of partnerships between professionals and patient-families.